Hydrothermal synthesis and characterisation of bioactive glass-ceramic nanorods - Zeimaran, E.; Pourshahrestani, S.; Shirazi, S.F.S.; Pingguan-Murphy, Belinda; Kadri, Nahrizul Adib; Towler, M.R. (Elsevier, 2016)
In this study fabrication of rod-like bioactive glass-ceramics (BGCs) using hydrothermal treatment based on a sol-gel precursor is reported for the first time. BGCs with composition 58 wt% SiO2, 33 wt% CaO and 9 wt% P2O5 were synthesized in different thermal conditions (200 and 220 °C) and characterised with regard to morphology, chemical composition and crystallinity. The bioactivity of the materials was assessed by immersion in simulated body fluid for up to 7 days. The results revealed that as the reaction temperature increased from 200 to 220 °C, the diameter of rods was reduced from microscale to nanoscale and the crystallinity was enhanced. It was also found that the BGC nanorods have higher surface area and consequently enhanced bioactivity than BGC microrods. This technique provides a facile method for rapid production of BGC nanorods at relatively low temperature which may have the potential to be used as bioactive composite reinforcement or for bone grafting applications.